Why Work? Our Ages-Old, Always-New Question. - Hicks, Stephen R. C. (Reason Papers)
The article explores the contrasting mindsets surrounding work, particularly why many successful individuals continue to work despite financial independence, while others view work as a burden. It discusses the impact of wealth and technology on perceptions of work, highlighting how advancements in robotics and artificial intelligence create both challenges and opportunities. The author references cultural narratives, such as biblical and mythological stories, that frame work as either a punishment or a means of self-realization. Additionally, it emphasizes the importance of critical thinking and problem-solving skills as essential for navigating the evolving job landscape, advocating for a shift in attitudes toward work as a vehicle for personal growth and fulfillment.